Visual Development of Chinese Children, Studied with Eye-Tracking Technology. Issue 2 (15th March 2019) - Liu, Jian; Xue, Lei
Abstract : Visual ability is important for the development of human intelligence and life abilities. In the process of receiving external information, the highest proportion comes through vision, up to 83 percent. Thus the healthy development of visual ability is crucial. Childhood is the main period for visual development. Eye-tracking technology can be used to study visual development in children. We therefore designed a complete experimental procedure and conducted visual developmental detection experiments on five children randomly selected from a Shanghai kindergarten. We investigated the eye data for each child experimentally. The parameters obtained from experimental data include saccadic times (ST), fixation points (FP), maximum fixation duration (MD), the highest incidence of sights passing the same point (NP), and the maximum number of fixations (MF). The parameters of the five children are scored and compared, and the results indicate that our experiments can analyze children's visual behavior and study children's visual development.